The Molecular Determinants of Mitochondrial Membrane Contact With ER, Lysosomes and Peroxisomes in Neuronal Physiology and Pathology - Liao, Yajin; Dong, Yuan; Cheng, Jinbo (Frontiers in Cellular Neuroscience, 2020)
Membrane tethering is an important communication method for membrane-packaged organelles. Mitochondria are organelles with a bilayer membrane, and the membrane contact between mitochondria and other organelles is indispensable for maintaining cellular homeostasis. Increased levels of molecular determinants that mediate the membrane contact between mitochondria and other organelles, and their functions, have been revealed in recent years. In this review, we aim to summarize the findings on the tethering between mitochondria and other organelles in physiological or pathological conditions, and to discuss their roles in cellular homeostasis, neural activity, and neurodegenerative diseases.